Keamanan dan Ancaman Cyber Bagi Sektor Privat dan Industry Militer Di Era 4.0 - Narindra, Krisna Surya (Universitas Perrtahanan Indonesia (UNHAN), 2021)
The development of the internet and digital technology is a representation of the 4.0revolution. The industrial revolution 4.0 shifts the role of humans and industrialmachines which characterized the Industrial Revolution that occurred before. Theeconomic policies of these countries to colonialization by Western European countries such as Britain, France and Germany and the United States were also the effects of the industrial revolution. Oil, metals, textiles supporting factories in the industrial revolution 1.0 to 3.0 the entry of these countries to invade, exploring countries that are rich in natural resource potential.Keyword: Keamanan siber, revolusi industry, ancaman dan keamanan siber,Artificial Inteligent